KOMUNIKASI EFEKTIF PIMPINAN DALAM MENGATASI KONFLIK ORGANISASI - Eti Sri Nurhayati; Aminah Swarnawati; Cahyo Wibowo; Eka Indri Widarti; Ahmad Thufail; Inasa Ori Sativa (Universitas Lambung Mangkurat, 2022)
The purpose of this research is to describe the effective communication performed by the leader in overcoming organizational conflicts at the Assistant Deputy for Policy Formulation for the Fulfillment of Children's Rights, the Ministry of Women Empowerment and Child Protection using the REACH Principle (Respect, Empathy, Audible, Clarity, Humble). The research uses a descriptive qualitative approach with a case study method. Data collection techniques were carried out through semi-structured interviews, observation and documentation. There were 4 informants, who were selected through purposive sampling and snowball sampling. The results showed that the communication used by the leadership using REACH principle was quite effective in overcoming organizational conflicts. Respect, leaders always listen to input, suggestions, opinions, complaints, stories, problems from all teams and open themselves to criticism and input. Empathy, the leader has a good enough sense of empathy so that it creates openness, and trust and seeks joint solutions if there is a conflict in the team. Audible, the leadership is considered quite clear in providing information and directions. Clarity, Leaders use the media for face-to-face meetings and zoom meetings during the Covid-19 Pandemic, and Whatsapp Group or private chat and telephone so that communication is clear and does not cause misunderstanding. Humble, the leader is very open and listens to all suggestions and input from team members and builds two-way communication to create a conducive work environment.